In Treatment with George Eliot - Bernstein, Susan (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2013)
While the psychoanalytic concept of transference is often the analytic crux of the interactions of the consulting-room, its structure also illuminates what transpires for readers and viewers of serial narratives. In Scenes of Clerical Life, Middlemarch, and In Treatment, the serial form prompts the back-and-forthness of transference and countertransference, much like our own fluctuating engagements between world and fiction. Ultimately this essay argues that the power of Victorian realism lies in its capacity to generate transference.